Using Housing Futures in Mortgage Research - Zhu, Shuang; Pace, R. Kelley; Morales, Walter A. (My University, 2014)
Expectations of housing prices play an important role in real estate research. Despite their importance, obtaining a reasonable proxy for such expectations is a challenge. The existing literature on mortgage research either does not include housing expectation proxies in empirical models, or uses “backward-looking” proxies such as past housing appreciation or time series forecasts based on past housing appreciation. This paper proposes to use the transaction prices of Case-Shiller housing futures as an alternative “forwardlooking” proxy. As an example, we compare the performances of four different expectation proxies in explaining mortgage default behavior. The loan level analysis shows that the futures based expectation proxy outperforms other proxies by having the highest regression model fit and being the only proxy that shows a significant negative effect on mortgage default behavior, as theory suggests. Out of sample predictions also show that futures have better prediction accuracy than other proxies. In addition, the paper shows that futures contain additional information that is not present in the backwardlooking proxies.
Keywords: Housing futures; Real estate futures; Housing expectation; House price expectation; Mortgage default